Neurobiology of Trauma Among Syrian Refugees in Lebanon: A Longitudinal Study 2011-2024 - M. Agung Rahmadi; Luthfiah Mawar; Sri Riska Handayani; Anggi Aminarti; Nazlah Khodijah; Nurzahara Sihombing; Rima Melati; Helsa Nasution; Annisa Ardianti Br Tarigan (Jurnal Medika Nusantara, 2025)
This meta-analysis synthesizes 47 longitudinal studies published between 2011-2024 to evaluate the dynamics of neurobiological changes in 12,847 Syrian refugees in Lebanon aged 6-65 years who were exposed to prolonged war-related trauma. The quantitative synthesis demonstrated significant reductions in hippocampal volume (r = -0.67, p < .001) and amygdala volume (r = -0.54, p < .001), observed in 78.4% of the sample, accompanied by an increase in cortisol levels up to 2.8 times the normal baseline. Dysregulation of the hypothalamic-pituitary-adrenal axis was detected in 81.2% of participants and showed a strong correlation with the severity of PTSD (r = 0.72, p < .001). Path analysis confirmed full mediation by dysfunction of the noradrenergic system (beta = 0.64, SE = 0.08, p < .001) in the relationship between trauma exposure and impaired memory function. Further meta-regression identified the duration of displacement as the most dominant moderator of neurobiological changes (Q = 24.37, df = 1, p < .001). In contrast to the findings of Mikhail et al. (2018) and Ruhnke et al. (2024), which emphasized social and environmental determinants, this study reveals specific neurobiological mechanisms underlying trauma in refugee populations, including a novel finding regarding distinctive patterns of default mode network connectivity that correlate with resilience (r = 0.58, p < .001). Overall, these findings extend the understanding of brain neuroplasticity within the context of chronic collective trauma.